Resilience of democracies: responses to illiberal and authoritarian challenges. Issue 5 (4th July 2021) - Merkel, Wolfgang; Lührmann, Anna
ABSTRACT: Illiberalism and authoritarianism have become major threats to democracy across the world. In response to this development, research on the causes and processes of democratic declines has blossomed. Much less scholarly attention has been devoted to the issue of democratic resilience. Why are some democracies more resilient than others to the current trend of autocratization? What role do institutions, actors and structural factors play in this regard? What options do democratic actors have to address illiberal and authoritarian challenges? This Special Issue addresses these questions. The present introduction sets the stage by developing a new concept of democratic resilience as the ability of a democratic system, its institutions, political actors, and citizens to prevent or react to external and internal challenges, stresses, and assaults. We sketch three potential reactions of democratic regimes: to withstand without changes, to adapt through internal changes, and to recover without losing the democratic character of its regime and its constitutive core institutions, organizations, and processes. The more democracies are resilient on all four levels of the political system (political community, institutions, actors, citizens) the less vulnerable they turn out to be in the present and future.